Central Post-Stroke Pain: An Integrative Review of Somatotopic Damage, Clinical Symptoms, and Neurophysiological Measures - Betancur, Daniel Fernando Arias; Tarragó, Maria da Graça Lopes; Torres, Iraci Lucena da Silva; Fregni, Felipe; Caumo, Wolnei (Frontiers in Neurology, 2021)
Introduction: The physiopathology of central poststroke pain (CPSP) is poorly understood, which may contribute to the limitations of diagnostic and therapeutic advancements. Thus, the current systematic review was conducted to examine, from an integrated perspective, cortical neurophysiological changes observed via transcranial magnetic stimulation (TMS), focusing on structural damage and clinical symptoms in patients with CPSP. Methods: The literature review included the following databases: EMBASE, PubMed, and ScienceDirect, using the following search terms by MeSH or Entree descriptors: [("Cerebral Stroke") AND ("Pain" OR "Transcranial Magnetic Stimulation") AND ("Transcranial Magnetic Stimulation")], through September 29, 2020. A total of 297 articles related to CPSP were identified. Of these, only four quantitatively recorded cortical measurements. Results: We found four studies with different methodologies and TMS measures results. According to National Institute of Health (NIH) guidelines, two studies had low methodological quality, and the other two studies had satisfactory methodological quality. The four studies compared motor threshold (MT) of the stroke-affected hemisphere with the unaffected hemisphere or with healthy controls. Two studies assessed other cortical excitability measures, such as cortical silent period (CSP), short- interval intracortical inhibition (SICI), and intracortical facilitation (ICF). The main limitations in the interpretation of the results were heterogeneity in parameter measurement, unknown cortical excitability measures as potential prognostic markers, the lack of a control group without pain, and the absence of consistent and validated diagnosis criteria. Conclusion: Despite the limited number of studies that prevented us from conducting a meta-analysis, the dataset of this systematic review provides evidence to improve the understanding of CPSP physiopathology. Additionally, these studies support the construction of a framework for diagnosis and will help to improve the methodological quality of future research in somatosensory sequelae following stroke. Furthermore, they offer a way to integrate dysfunctional neuroplasticity markers that are indirectly assessed by neurophysiological measures with their correlated clinical symptoms.